Investigation of silica crystallization kinetics in rice husk ash for sustainable construction materials - Abbas Muhammad Aun; Hoe Kwan Wai; Bin Samsudin Muhammad Hasnolhadi (E3S Web of Conferences)
Concrete is one of the most widely used materials in the world, and its utilization is rising drastically with the increasing population. Around 5-8% of global carbon emissions are caused by cement production. On the other hand, approximately 160 million tons of rice husk, considered agrowaste, turn into ash annually. Rice husk ash (RHA) is particularly attractive due to its high silica content and great potential to be used as a cementitious material. However, impurities such as alkali metal oxides and uncontrolled combustion reduce the quality of silica and promote its crystallization. Numerous studies have focused on obtaining active silica through acid leaching to remove impurities, but the study on the reaction kinetics of functionalized rice husk ash is very limited. In this research, 0.1M hydrochloric acid (HCl) was used to leach rice husk at temperatures of 50°C, 60°C, and 70°C for 1.5 hours. The rice husk was then burned at 800°C for 2 hours. Subsequently, the ash was examined using various analytical and computational techniques to develop an in-depth understanding of the burning process, aimed at producing functionalized amorphous silica for sustainable construction. It was observed that 99.39% silica with 95.04% amorphous content was formed by treating rice husk with 0.1M HCl at 70°C for 1.5 hours, followed by combustion at 800°C for 2 hours. Furthermore, reaction kinetics parameters were identified using the Coats-Redfern kinetic model for the two different reaction zones of the burning process.